THE INFLUENCE OF WORK MOTIVATION, WORK ENVIRONMENT, AND WORK-LIFE BALANCE ON THE PERFORMANCE OF EMPLOYEES IN THE FORESTRY BRANCH OFFICE OF CENTRAL JAVA PROVINCE, REGION VI (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Employee performance is considered a crucial factor in the sustainability and success of a company. The higher the performance level of an employee, the greater the achievement of company goals will be. This research aims to determine the influence of work motivation, work environment, and work-life balance on the performance of employees in the Forestry Branch Office of Central Java Province, Region VI. The research sample consists of 50 individuals, all of whom are employees of the Forestry Branch Office of Central Java Province, Region VI, using a saturated sampling method. The data analysis techniques in this study include validity testing, reliability testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results of this research are expected to provide a deeper understanding of the factors affecting employee performance and serve as a basis for improvements in human resource management.
Keywords: Work Motivation; Work Environment; Work-Life Balance; Performance